East Asia Integrates : A Trade Policy Agenda for Shared Growth - Krumm, Kathie; Kharas, Homi (Washington, DC: World Bank and Oxford University Press, 2013)
Rapid and sustained growth in international trade has long been a hallmark of successful growth and development strategies in East Asia. Some success stories are well known: those of the newly industrializing economies (NIEs) such as the Republic of Korea, as well as middle-income economies such as Malaysia and the transition economy of China. More recent entrants to world markets that have seen rapid export growth include low-income economies such as Cambodia and Vietnam. Trade has been an important factor in growth in the region, enabling progress in poverty reduction. Although the 1997-98 financial crisis interrupted this progress, recovery since then has brought poverty rates in every emerging economy in the region to record lows, and in economies like that of Vietnam, trade growth has brought with it a rapid reduction in poverty. Intraregional trade in East Asia has grown faster than trade with any other market, and while the largest economies account for the bulk of this trade, the regional trade of most smaller economies has also grown. Trade integration has been marketled, stemming from a combination of unilateral reforms, fulfillment of multilateral commitments, and a pattern of relocation of production processes (see Kawai and Urata 2002). Intraregional trade has been driven not only by growing demand but increasingly by improved competitiveness in regional markets, as reflected in increased market shares (Figure 1). China has been particularly dynamic, but almost all countries increased their competitiveness in regional markets during 1995-2001.9 This increase was accomplished without loss of competitiveness in other markets; East Asia continued to expand its market shares in the European Union (EU) and North American Free Trade Agreement (NAFTA) markets in the same period.